PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW BERBANTUAN MEDIA POP UP BOOK UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS VIII SMP NEGERI SATAP WALATUNGGA - Rambu Kata, Meliati; Makaborang, Yohana; Njoereomana, Yohana (Universitas Cokroaminoto Palopo, 2025)
The purpose of this study is to describe the improvement in learning outcomes after implementing the jigsaw type Cooperative learning model assisted by pop up book media to improve the learning outcomes of class VIII students of Smp Negeri Satap Walatungga. This type of research is a type of classroom action research with a descriptive quantitative approach. The research was conducted in class with cycles. The stages of the research are: planning, implementation, observation and reflection. The subjects of this research were class VIII students of Smp Negeri Walatungga. In this study, the researcher used quantitative data analysis techniques. Quantitative data comes from the results of the post-test, multiple choice at the end of each cycle obtained from the results of tests given by the teacher to students to determine the extent to which student learning outcomes have improved. Data analysis techniques include calculating the average value, calculating the completeness of student learning cognitive assessment and calculating the completeness of student learning affective assessment. The results of the study are seen from the comparison of the average values ​​of each cycle in the pre-cycle 56.40, cycle 56.46, and cycle II 62.90. These results can be said to have increased. It can be concluded that the application of the jigsaw type cooperative learning model assisted by pop-up book media can improve the learning outcomes of class VIII students at SMP Negeri Satap Walatungga.